2013
DOI: 10.1371/journal.pone.0060687
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-27b Targets Vascular Endothelial Growth Factor C to Inhibit Tumor Progression and Angiogenesis in Colorectal Cancer

Abstract: Colorectal cancer (CRC) is one of the most prevalent cancers globally and is one of the leading causes of cancer-related deaths due to therapy resistance and metastasis. Understanding the mechanism underlying colorectal carcinogenesis is essential for the diagnosis and treatment of CRC. microRNAs (miRNAs) can act as either oncogenes or tumor suppressors in many cancers. A tumor suppressor role for miR-27b has recently been reported in neuroblastoma, while no information about miR-27b in CRC is available. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
95
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(106 citation statements)
references
References 41 publications
10
95
0
1
Order By: Relevance
“…Multiple targets have been identified for members of the miR-23b/27b/24 cluster, including SPRY, ANXA2, ARHGEF6, CFL2, LIMK2, PIK3R3, PLAU, VEGFC, PTPN9, and PTPRF (21)(22)(23)(24). We have additionally uncovered the direct targeting of PSAP by miR-24 and miR-27b.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Multiple targets have been identified for members of the miR-23b/27b/24 cluster, including SPRY, ANXA2, ARHGEF6, CFL2, LIMK2, PIK3R3, PLAU, VEGFC, PTPN9, and PTPRF (21)(22)(23)(24). We have additionally uncovered the direct targeting of PSAP by miR-24 and miR-27b.…”
Section: Discussionmentioning
confidence: 76%
“…Similarly, miR-24 has been shown to inhibit apoptosis and promote the formation of micrometastases within the lungs of subcutaneously injected mice (23). Finally, although miR-27b has been shown to decrease primary colorectal cancer tumor growth and inhibit angiogenesis (24), miR-27a has been shown to positively correlate with breast cancer progression (25). Thus, the miR-23ab/27ab/24 miRNAs have been shown to possess dichotomous roles during tumor progression.…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
“…Some highly expressed miRs may function as oncogenes by repressing tumor suppressor genes, whereas lowly expressed miRs may function as tumor suppressors by negatively regulating oncogenes. In terms of CRC, abnormal expression of several miRs such as miR-27b, miR-133b, miR-124 have been reported (Ye et al, 2013;Zhang et al, 2013b;Xiang and Li, 2014). Additionally, Zhang et al (2013a) found that ectopic expression of miR-224 promoted CRC tumor cell proliferation, migration, and invasion in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, suggesting that miR-27b may act as a tumor inhibitor in NSCLC. Previous studies have revealed that miR-27b acts as a tumor suppressor in the development of various malignancies, including prostate cancer, colon cancer and neuroblastoma (24)(25)(26). However, other studies have also indicated that miR-27b may promote tumorigenesis in various cancer types.…”
Section: Discussionmentioning
confidence: 99%